Complementary and alternative medicine use by diabetic patients in rural Bengaluru - K. R., Vidya; K., Lohit (International Journal Of Community Medicine And Public Health, 2019)
Background: Complementary and alternative medicine (CAM) use is common among patients with chronic diseases in developing countries. The rising use of CAM in the management of diabetes is an emerging public health concern given the potential adverse effects, drug interactions and benefits associated with its use. The main objective of this study is to determine the prevalence regarding complementary and alternative medicines among diabetic patients and to assess the perception and factors influencing use of complementary and alternative medicines among diabetic patients. Methods: A community based cross sectional study including diabetic subjects aged more than 18 years was conducted in the rural area of Bengaluru Expecting the prevalence of CAM use to be 67% as with Kumar et al, a minimum of 136 subjects were required to conduct study. Data from 150 diabetic subjects were collected during house to house visit in rural area by using a pre structured questionnaire. Diabetic subjects were randomly selected using multi stage random sampling method. Results: Most of the participants (80%) were aware of CAM and prevalence of CAM use was 54.6%. Significantly the use of CAM was more among females, literates, with diabetic complications and with family history of DM. The common source of information on CAM was friends (45.8%) and neighbors (25.8%). Desire for the quick and additional relief, low cost and easy availability was the prime factors influencing use of complementary and alternative medicines. Conclusions: The prevalence of CAM use among diabetic patients is high. Physicians need to understand CAM better and communicate more with patients.